Digital technology supports healthcare in disaster emergency management in remote areas of Indonesia - Abil Rudi; Kafi Pangki Suwito (JOURNAL OF Medical Surgical Concerns, 2026)
Background: Remote areas of West Kalimantan face significant geographical barriers that result in delayed nursing response times during disaster emergencies. Digital technology adoption serves as a strategic innovation to accelerate coordination and nursing interventions in these resource-limited settings. Purpose: To analyze the influence of digital technology adoption on nursing response time in emergency disaster management in remote areas of West Kalimantan. Method: A cross-sectional study was conducted involving 320 nurses at health facilities in remote areas of West Kalimantan, selected through simple random sampling. Technology adoption was measured using a validated questionnaire, while digital response time was assessed through structured observation. Data analysis employed simple linear regression to examine the relationship between technology adoption and digital response time. Results: The findings indicate that technology adoption levels were high among respondents (71.2%). The average nursing response time was 10.8 minutes, demonstrating significant improvement compared to conventional systems. Simple linear regression analysis revealed that technology adoption significantly influenced nursing response time (p < 0.001), explaining 43.5% of the variance (R² = 0.435). Communication signal instability at specific geographic locations was identified as a primary constraint. Conclusion: Digital technology adoption significantly enhances nursing response time in emergency disaster management in remote areas. Integration of technology-based emergency nursing curricula and strengthened digital infrastructure in remote settings are essential to support patient safety during disaster emergencies.